Faktor-Faktor yang Mempengaruhi Siklus Menstruasi pada Remaja Putri - Sequeira, Jenia Paula; Suryantara, Bima; Sari, Fatimah (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the factors that influence the menstrual cycle in adolescent girls at SMA Negeri 2 Ngaglik, explicitly analyzing the influence of body weight, physical activity, and anxiety in teenage girls at SMA Negeri 2 Ngaglik. The method used is quantitative research with descriptive methods and a cross-sectional design. The research results show a significant relationship between body weight and menstrual cycle irregularities with a p-value of 0.001, so the p-value is <0.05. There is an essential relationship between physical activity and menstrual cycle irregularities with a p-value of 0.000, so the p-value is <0.05. There is a significant relationship between anxiety and menstrual cycle irregularities, with a p-value of 0.001 with a p-value <0.05. In conclusion, body weight, physical activity, and anxiety influence menstrual cycle irregularities in young women at SMA Negeri 2 Ngaglik. Keywords: Physical Activity, Body Weight, Menstrual Cycle, Anxiety